Presoaking Treatment of Soybean [Glycine max (L.) Merrill] Seeds Using Fermented Plant Extracts and Commercial Liquid Fertilizer - Cejalvo, Reneliza; Mercado, Maria Fatima O. (JPAIR Multidisciplinary Research, 2018)
The yield of soybean in the Philippines is significantly low. Presoaking is one of the seed priming techniques to improve seed quality. This study aimed to determine the effects of selected fermented plant extracts and commercial organic fertilizer on germination and vigor of soybean seeds. The seeds presoaked in organic agriculture inputs such as ipil ipil FPJ (Fermented Plant Juice), squash FFJ (Fermented Fruit Juice), commercial organic fertilizer (PSPLOF), and water (control). The seeds were then subjected to seed quality tests to evaluate germination and vigor. Ipil ipil FPJ and squash FFJ significantly improved the percentage germination, first count, vigor index, seedling growth, and seedling emergence. Commercial fertilizer showed poor results in seed germination and vigor tests. Seeds soaked in water showed high percentage germination but have poor vigor. Data were arranged in factorial in Completely Randomized Design (CRD) and analyzed using Analysis of Variance (ANOVA). The initial seed quality results revealed significantly poor germination and vigor. Therefore, presoaking of soybean seeds in ipil ipil FPJ and squash FFJ is recommended to improve the germination and vigor of soybean seeds. The results could be useful to reduce the cost of soybean production and to enhance the yield of soybean.
Keywords: Agriculture; agronomy; soybean; seed germination; seed vigor; seed priming; seed presoaking; Asia; Philippines